Influence of domestic sewage leakage on the collapse of tropical soils - Rodrigues, Roger Augusto; de Lollo, Jose Augusto (Springer, 2007)
In the studied region, 35% of the soil collapses are related to leakage from sewage ducts. The paper describes the soils from this part of Brazil and a series of laboratory tests undertaken using water and domestic sewage fluid as the wetting agents. It is considered that the presence of soaps and detergents as recorded by the sodium concentration facilitates the densification of the soils and hence has a major effect on the surface settlement/collapse.
Keywords: tropical soils; collapsible soils; domestic sewage; scanning electric microscopy; consolidation test